Is there consumer risk-pooling in the open economy? The evidence reconsidered - Patrick Minford; Zhirong Ou; Zheyi Zhu (Cardiff University, Cardiff Business School, 2020)
We revisit the evidence on consumer risk-pooling and uncovered interest parity. Widely used singleequation tests are strongly biased against both. Using the full-model, Indirect Inference test, which is unbiased and has Goldilocks power by Monte Carlo experiments, we find that both the risk-pooling hypothesis and its weaker UIP version are generally accepted as part of a full world DSGE model.The fact that the risk-pooling hypothesis, with its implication of strong cross-border consumer linkage,has passed this test with generally the highest p-value, suggests that it deserves serious attention from policy-makers looking for a relevant model to discuss international monetary and other business cycle issues.
Keywords: C12; E12; F41; 330; Open economy; consumer risk-pooling; UIP; full-model test; IndirectInference